Identifying Research Trends and Gaps in the Context of Linux and Unix Security - Adriano, Raquel C.; Calayag, Jahleine Marielle M.; Cruz, Marian Minelli S.; Concepcion, Anthony U. (Future Science / FSH-PH Publications, 2025)
Linux and Unix operating systems are fundamental to modern computing infrastructures, including cloud platforms, mobile devices, and supercomputers. With their increasing adoption, security has remained a persistent and evolving concern over the past two decades. This study conducts a systematic bibliometric analysis of 50 peer-reviewed journal articles and conference papers published between 2001 and 2020, segmented into four time periods: 2001–2005, 2006–2010, 2011–2015, and 2016–2020. Using citation analysis and co-word mapping via Mendeley and VOSviewer, the study identifies four main thematic clusters: (1) access control and authentication, (2) kernel-level vulnerabilities, (3) cloud and container security, and (4) mobile and Android-related threats. Early research focused on foundational topics such as system architecture and access control mechanisms, while more recent studies emphasized cloud-native security, virtualization, and mobile platform vulnerabilities. The analysis also reveals a significant disparity in research volume, with Linux-related studies dominating the field and Unix security receiving less than 20% of the total focus. This underrepresentation of Unix indicates a critical gap in the literature. These findings highlight not only the shifting priorities in open-source operating system security but also the need for renewed attention to Unix-specific threats and cross-platform security strategies in future research.